Natriuretic peptide and exercise - Kazuhiro Suda (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Natriuretic peptide (NP) release is mainly stimulated by stretching of the myocardium. NP causes diuresis, natriuresis and vasodilation. NP release increases during exercise. Increased NP plays a counter-regulatory role in increased blood pressure during exercise and makes it lower. The source of ANP released during exercise seems to depend on the experimental conditions. Exercise affected guanylate cyclase activity in the kidney and adrenals. Plasma NP concentration is increased in the hypertensive state. Also, exercise increases plasma NP concentration. But when hypertensive model rats swim for more than 30 minutes, plasma ANP concentration decreases to below the resting level.